Ten-year-and-beyond longitudinal change of ß-zone parapapillary atrophy in glaucoma: association with retinal nerve fibre layer defect. Issue 10 (30th April 2021) - Bak, Eunoo; Kim, Yong Woo; Kim, Young Kook; Jeoung, Jin Wook; Park, Ki Ho
Abstract : Background: To investigate the longitudinal change of localised retinal nerve fibre layer (RNFL) defects associated with change of ß-zone parapapillary atrophy (PPA) in primary open-angle glaucoma (POAG) eyes. Methods: POAG patients with a localised RNFL defect and ß-zone PPA who had undergone disc/RNFL photography at 1-year intervals for 10 years or longer were enrolled. The topographic parameters of ß-zone PPA (area, maximal radial extent and angular extent around disc) were measured. Progression of RNFL defect was defined as widening of defect and/or appearance of new defect. The factors associated with progression of RNFL defect were assessed by OR using multivariable logistic regression. Results: A total of 209 patients (209 eyes) with POAG were included (mean: 54 years old). Over the course of 11.5±2.3-year follow-up period, progression of RNFL defect was detected in 114 eyes (54.5%). Enlargement of PPA parameters (area and angular extent) was significantly more common in patients with RNFL defect progression than in eyes without progression (all p<0.001, respectively). Widening of radial extent did not show a significant difference in both groups (p=0.61). Increment of angular extent was in the direction of RNFL defect progression in 82.1% of eyes. Progression of RNFL defect was significantly associated with disc haemorrhage (OR: 6.653, p<0.001), enlargement of PPA area (OR: 4.114, p=0.004) and angular extent (OR: 6.572, p<0.001). Conclusions: Progression of RNFL defect is associated with increment of angular extent of PPA in POAG eyes.